Susceptibilidade ao vírus da mionecrose infecciosa (IMNV) de juvenis de camarões Penaeus vannamei cultivados sob diferentes densidades em sistema simbiótico - Silva, Giselle Adayllana de Vasconcelos (2023)
Viral etiologic agent diseases affected and still affect Brazilian shrimp production, such as Infectious Myonecrosis (IMN). The establishment of a microbiological and environmental balance in culture systems can allow optimal growth conditions, especially in the early stages of shrimp development, when the animal's immune system is still developing. The fewer challenges encountered in this phase, the greater productive efficiency can be observed. That said, the present work had as general objective to evaluate the susceptibility of juveniles of Penaeus vannamei shrimp cultivated in a symbiotic system to the experimental challenge with IMNV. The methodology consisted of carrying out a viral challenge through the oral administration (i.e., per os) of tissue contaminated with IMNV using juvenile marine shrimp from different cultivation densities in symbiotic systems. Survival data and verification of clinical signs of IMN were recorded throughout the experiment and lasted for 30 days. For molecular analyses, collections were performed on the 0, 7th, 14th and 21st days post-infection (d.p.i). For histopathological analyses, shrimp samples collected and fixed at 21° d.p.i were observed. The mortality curves showed no statistical difference between the survival curves of the 6 PL/L - I group and the control group (p>0,05), but significantly different from the 2 PL/L - I and 4 PL/L - I groups (p<0,05). Histopathological alterations suggestive of IMN were not observed in animals belonging to the control group. In the group of challenged shrimp, tissue lesions characteristic of the disease were observed. The experimental challenge per os proved to be efficient for the establishment of an infectious process in juveniles of P. vannamei; animals grown at a density of 6 PL/L in symbiotic culture systems were less susceptible to IMNV when compared to animals from symbiotic cultures at lower densities (2 PL/L and 4 PL/L). Molecular diagnosis results were inconclusive and variable among themselves. Based on the histopathological and molecular analyzes carried out in the present study, it is recommended viral isolation and/or DNA sequencing of the samples obtained during the experimental challenge in order to identify new IMNV variants or new pathogens that may cause damage brazilian shrimp farming.